Cymbeline : king of Britain [Cymbelín kráľ Británie anglicky] - Shakespeare, William, 1564-1616; Shakespeare, William, 1564-1616.; Macaw Books (Leicester : Sweet Cherry Publishing, 2020)
"Cymbeline, King of Britain" is one of the best-known works of William Shakespeare. It is a romantic play interwoven with war and tragedy. It revolves around Cymbeline and his daughter, Imogen. Imogen does not abide by her her father´s wishes, and marries a lowborn gentleman, Posthumous. After their marriage, Psthumous is banished from Britain and Imogen is held as a prisoner in the palace. As the play unfolds, the evil plots of the queen, Imogen´s stepmother, the jealousy of Posthumous and the loyalty of Imogen come to light.
A short narrative version of the play has been suitably adapted to help to introduce the play to young readers.
Keywords: Great Britain -- Pictorial works -- Juvenile fiction. -- Kings and rulers; Children's stories -- Pictorial works; čítam si sám (7+); cudzojazyčná literatúra